Association between full monitoring of biomedical and lifestyle target indicators and HbA1c level in primary type 2 diabetes care: an observational cohort study (ELZHA-cohort 1). Issue 3 (13th March 2019) - van Bruggen, Sytske; Rauh, Simone P; Kasteleyn, Marise J; Bonten, Tobias N; Chavannes, Niels H; Numans, Mattijs E
Abstract : Objective: Management of type 2 diabetes mellitus (T2DM) requires frequent monitoring of patients. Within a collective care group setting, doubts on the clinical effects of registration are a barrier for full adoption of T2DM registration in general practice. We explored whether full monitoring of biomedical and lifestyle-related target indicators within a care group approach is associated with lower HbA1c levels. Design: Observational, real-life cohort study. Setting: Primary care data registry from the Hadoks (EerstelijnsZorggroepHaaglanden) care group. Exposure: The care group provides general practitioners collectively with organisational support to facilitate structured T2DM primary care. Patients are offered quarterly medical and lifestyle-related consultation. Main outcome measure: Full monitoring of each target indicator in patients with T2DM which includes minimally one measure of HbA1c level, systolic blood pressure, LDL, BMI, smoking behaviour and physical exercise between January and December 2014; otherwise, patients were defined as 'incompletely monitored'. HbA1c levels of 8137 fully monitored and 3958 incompletely monitored patients were compared, adjusted for the confounders diabetes duration, age and gender. Since recommended HbA1c values depend on age, medication use and diabetes duration, analyses were stratified into three HbA1c profile groups. Linear multilevel analyses enabled adjustment for general practice. Results: Compared with incompletely monitored patients, fully monitored patients had significantly lower HbA1c levels (95% CI) in the first (−2.03 [−2.53 to −1.52] mmol/mol) (−0.19% [−0.23% to −0.14%]), second (−3.36 [−5.28 to −1.43] mmol/mol) (−0.31% [−0.48% to −0.13%]) and third HbA1c profile group (−1.89 [−3.76 to −0.01] mmol/mol) (−0.17% [−0.34% to 0.00%]). Conclusions/interpretation: This study shows that in a care group setting, fully monitored patients had significantly lower HbA1c levels compared with incompletely monitored patients. Since this difference might have considerable clinical impact in terms of T2DM-related risks, this might help general practices in care group settings to overcome barriers on adequate registration and thus improve structured T2DM primary care. From population health management perspective, we recommend a systematic approach to adjust the structured care protocol for incompletely monitored subgroups.